Ecological justice in environmental criminal sanctions for corporations in Indonesia: Problems and Solution - Saputra, Rian; Usada, Albertus; Islam , Muhammad Saiful (Journal of Law, Environmental and Justice, 2024)
This study examines the ecological justice approach to imposing criminal sanctions on corporations in Indonesia for environmental crimes. The author also discusses the challenges associated with implementing this approach and aims to explain the measures and principles involved in regulating sanctions for environmental crimes committed by corporations while ensuring a balance between ecological justice and legal certainty. This study employs a normative legal research methodology, utilising a case-based approach, a statutory approach, and a conceptual approach. The research findings indicate that the regulation of fines for environmental restoration has implemented an ecological justice strategy focused on safeguarding the environment. Nevertheless, there are concerns regarding legal certainty in addressing the balance between ecological justice and legal certainty. This can be achieved through various means, including a. incorporating effective measures and specific types of improvement into criminal sanctions for environmental restoration and b. prioritising additional criminal sanctions for environmental restoration as the primary form of punishment while taking into account the importance of legal certainty.